2013
DOI: 10.1016/j.techfore.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management systems in support of disasters management: A two decade review

Abstract: Humans are increasingly being challenged with numerous forms of man-made and natural emergency situations. Emergencies cannot be prevented, but they can be better managed. The successful management of emergency situations requires proper planning, guided response, and well-coordinated efforts across the emergency management life cycle. Literature suggests that emergency management efforts benefit from well-integrated knowledge-based emergency management information systems (EMIS). This study presents a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 54 publications
2
69
0
1
Order By: Relevance
“…Compared to previous work in information and knowledge management applications for emergency support (e.g. Dorasamy et al, 2013), social media have created much more open and ubiquitous information flows between authorities and the public. This is one of the reasons why Turoff et al (2013) more specifically suggest that social media merit further attention with regard to their potential to engage with the public during emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to previous work in information and knowledge management applications for emergency support (e.g. Dorasamy et al, 2013), social media have created much more open and ubiquitous information flows between authorities and the public. This is one of the reasons why Turoff et al (2013) more specifically suggest that social media merit further attention with regard to their potential to engage with the public during emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…It provides valuable input to both theory and methodological practice for the design and development of ISs for fire ER with the possibility of extending to other similar crises. This contribution is further justified by the findings of the systematic literature review of investigating emergency management information systems in last two decades (Dorasamy et al, 2013). In the literature reviewed, among nearly 50 systems supporting emergency management, SafetyNet was the only system that supports firefighters.…”
Section: Implications For Theory and Practicementioning
confidence: 98%
“…This includes ISAs for supporting fire emergencies. Examples include the work of Wilson et al (2005) and Wilson et al (2007) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Dorasamy et al (2013) clearly indicate that except for SafetyNet (n.d.), which is the system associated with the ISA proposed in the current paper, there had been no other significant, directly relevant research in this area as at 2013. In particular Dorasamy et al (2013) reported no other significant research regarding information systems for supporting various firefighting job roles.…”
Section: Page 2 Of 34 Journal Of Enterprise Information Managementmentioning
confidence: 99%
“…This work gives careful consideration to a basic and guaranteed calculation for finding utilizing RFIDs [36] Review of Emerging Technologies to Support Urban Resilience and Disaster Recovery…”
mentioning
confidence: 99%
“…Healthcare and Disaster Supply Chain: Literature Review and Future Research [36] The labeled patients' area will be naturally followed and overhauled on the interface Smartphone and RFID tag based rescue.…”
mentioning
confidence: 99%